Study on Chemical Genesis of Deep Geothermal Fluid in Gaoyang Geothermal Field - Xing, Yifei; Yu, Haowen; Liu, Zhao; Li, Jie; Liu, Shaoyun; Han, Sihang; Wang, Guiling (Frontiers in Earth Science, 2022)
Abstract： Geothermal resources are clean energy with a great potential for development and utilization. Gaoyang geothermal field, located in the middle of raised area in Hebei province, China, is one of the three major geothermal fields in Xiong'an New Area. With the development of Xiong’an New Area, this geothermal field has become a research hotspot. According to the latest survey, the bottom-hole temperature of the D34 and D35 in the north of Gaoyang geothermal field is 149℃ and 116℃, respectively, which indicates favorable target areas for geothermal exploitation The circulation mechanism and chemical origins of geothermal fluid are unclear in the Gaoyang geothermal field, which hinders the evaluation of geothermal resources in this region. Therefore, the water chemical and isotopic study were performed in the Gaoyang geothermal fluid to understand the genesis of Gaoyang geothermal field. Piper trigram and Na-K-Mg software were also used to explore the genesis of underground hot water. Combined with stratigraphy and geothermal geology, it can be concluded that the primary hydrochemical type of Gaoyang geothermal field is Na-HCO3·Cl type. In the process of upward migration of geothermal water, leaching and cation alternating adsorption took place, and finally high TDS geothermal water was formed. Our results are helpful for geothermal resource evaluation and utilization, and provide scientific guidance for sustainable development of geothermal resources.